Three-dimensional graphene materials : preparation, structures and application in supercapacitors - Cao, Xiehong (2014)
Three-dimensional (3D) graphene materials (3DGMs) are of great importance due to their unique properties and practical applications. A number of 3DGMs with novel structures have been developed in recent years. This review presents the current progress of 3DGMs. After introducing the preparation strategies of 3DGMs, we summarize the reported 3DGMs based on their different structures, and then focus on the description of their preparation methods, properties and applications. Lastly, the applications of 3D graphene-based materials in supercapacitors are described.